Phenolic compounds from Anomianthus dulcis - Andrea Sinz (2018)
p-Coumaroyl-β-phenethylamine (1) and 2',3'-dihydroxy-4',6'- dimethoxydihydrochalcone (2) were isolated by preparative HPLC from a methanolic extract of Anomianthus dulcis leaves. This is the first time that these compounds were isolated from a natural source. In addition, the known compounds chrysin (3), pinocembrin (4), 5,7-dimethoxy-8-hydroxyflavanone (5) and 2',3'-dihydroxy-4',6'-dimethoxychalcone (6) were isolated for the first time from the genus Anomianthus. The isolated compounds were identified by1H and13C NMR, MS, UV and IR.